Risk, risk reduction and management of occult malignancy diagnosed after uterine morcellation: a commentary. (November 2015) - Lynam, Sarah; Young, Laura; Morozov, Vadim; Rao, Gautam; Roque, Dana M
Minimally invasive surgical techniques compared with laparotomy offer the advantages of less intraoperative blood loss, shorter hospitalization, fewer wound complications and faster return to baseline activity for both hysterectomy and myomectomy. While morcellation allows for the laparoscopic removal of large specimens, it may result in intraperitoneal dissemination of benign disease or upstaging of occult malignancy leading to compromised survival. There has been heightened scrutiny over appropriate patient selection and preoperative assessment in light of recent warnings against power morcellation issued by the US FDA. This commentary therefore summarizes the magnitude of such risks associated with uterine morcellation, current national regulatory statements and potential merits of risk-reducing approaches such as contained morcellation. The importance of patient counseling is underscored.